The Mohawk Crisis: A crisis of hegemony. An analysis of media discourse. - Stuart, Charles. (University of Ottawa (Canada), 1993)
The subject for this thesis was the Mohawk Crisis at Oka, Quebec during the summer of 1990. The theoretical framework underlining the study was Antonio Gramsci's concept of a crisis of hegemony or legitimation crisis as applied by Stuart Hall et al. (1978). Within this theoretical framework the media are viewed as an ideological mechanism perpetuating the existing hegemonic relationship. The research undertook to apply this social theory to the Mohawk Crisis and examine the ideological discourse in the media coverage of the Crisis. Press reports taken from the Globe and Mail and Montreal Gazette were analyzed using quantitative content analysis and a qualitative exploratory technique. The following two general theses were examined: firstly, that ideological discourse would be apparent in media coverage of the 1990 Mohawk Crisis and, secondly, that the media supported an official 'law and order' campaign during the Mohawk Crisis. Further, two more specific hypotheses were tested in individual chapters which present the results of the quantitative content analysis. (Abstract shortened by UMI.)
Keywords: History, Canadian.